Emerging Biomarkers for Predicting Bladder Cancer Lymph Node Metastasis - Zhang, Chunyu; Hu, Jiao; Li, Huihuang; Ma, Hongzhi; Othmane, Belaydi; Ren, Wenbiao; Yi, Zhenglin; Qiu, Dongxu; Ou, Zhenyu; Chen, Jinbo; Zu, Xiongbing (Frontiers in Oncology, 2021)
Bladder cancer is one of the leading causes of cancer deaths worldwide. Early detection of lymph node metastasis of bladder cancer is essential to improve patients’ prognosis and overall survival. Current diagnostic methods are limited, so there is an urgent need for new specific biomarkers. Non-coding RNA and m6A have recently been reported to be abnormally expressed in bladder cancer related to lymph node metastasis. In this review, we tried to summarize the latest knowledge about biomarkers, which predicts lymph node metastasis in bladder cancer and their mechanisms. In particular, we paid attention to the impact of non-coding RNA on lymphatic metastasis of bladder cancer and its specific molecular mechanisms, as well as some prediction models based on imaging, pathology, and biomolecules, in an effort to find more accurate diagnostic methods for future clinical application.